Pulse Wave Velocity in Association with Cognitive Function - Zhong, PhD, Wenjun (North American Journal of Medicine and Science, 2011)
Dementia is an important public health issue in the ageing society; however the cause of dementia has not been clear yet except for age and genes. Cardiovascular risk factors have been suggested to contribute to dementia, such as high blood pressure, but the evidence from clinical trials has not been conclusive. The biological mechanism of cardiovascular disorders in association with cognitive function needs further study. Aortic pulse wave velocity (PWV), a “gold standard” measurement of arterial stiffness, has been established as an independent predictor of CVD events. Understanding the association of PWV and cognitive function can further help to understand the role of vascular risk factors in cognitive decline and dementia. Studies on the association of PWV and cognitive function have emerged recently. This manuscript introduced the measurement of aortic PWV, summarized the studies of its association with cognitive function, and commented on the possible mechanism of the association between arterial stiffness and cognitive function. Because of the link between cardiovascular disorders and dementia, intervention of cardiovascular risk factors may have additional benefits on cognitive function with ageing.